2008
DOI: 10.1038/sj.jp.7211914
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole prophylaxis for prevention of invasive fungal infections in targeted highest risk preterm infants limits drug exposure

Abstract: Objective: Previous reports suggest a benefit of fluconazole prophylaxis in extremely low birth weight (ELBW) infants <1000 g. Our aim was to evaluate if limiting fluconazole prophylaxis to targeted highest risk infants effectively prevents invasive fungal infections, has no undesired side effects and limits unnecessary drug exposure.Study Design: This nonrandomized retrospective pre-post intervention study compared two groups of infants: (1) Infants <26 weeks gestation and/or <750 g birth weight, requiring ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 28 publications
2
41
0
1
Order By: Relevance
“…In infants weighing under 1000 g with ICI, mortality rates range from 23 to 66% of the control patients in prophylaxis studies [5][6][7][8][9][10][11][12][13][14][15]. There is a marked difference in mortality between infants weighing under 1000 g and larger infants with ICI.…”
Section: Scope Of the Problemmentioning
confidence: 97%
See 1 more Smart Citation
“…In infants weighing under 1000 g with ICI, mortality rates range from 23 to 66% of the control patients in prophylaxis studies [5][6][7][8][9][10][11][12][13][14][15]. There is a marked difference in mortality between infants weighing under 1000 g and larger infants with ICI.…”
Section: Scope Of the Problemmentioning
confidence: 97%
“…Weitkamp et al recently reported the importance of examining ICI incidence in each NICU, as many flaws exist when solely relying on the literature for incidence rates [15]. The NICU reported that their rate of Candida BSI was 6.8%, while the rate of all ICIs was 10% for infants weighing under 1000 g.…”
Section: What Is the Incidence Of Ici In Your Nicu?mentioning
confidence: 99%
“…Rates of invasive candidiasis in two randomized controlled trials and one targeted retrospective study ranged from 13.2 to 20%. 6,13,15 A much lower incidence of 7% Candida bloodstream infections is reported among the NICHD Neonatal Research Network centers for PT infants with birth weights <1000 g. 1 According to the National Mycoses Study Group, 3.1% of VLBW (<1500 g) infants develop Candida bloodstream infections, whereas a 1% rate were reported in the UK prospective surveillance study. 21,22 Whether our results can be extrapolated to other centers with low rates remains to be determined.…”
Section: Targeted Fluconazole Prophylaxis In Preterm Infantsmentioning
confidence: 99%
“…The OR for invasive fungal infection was similar to 4-to 6-week fluconazole courses, with a lower number of doses (median 6) per infant; 51% of all VLBW infants received prophylaxis. Weitkamp et al 15 used a targeted approach of FP to 42 PT infants (<750 g birth weight or <26 weeks gestational age with a central line access) for 6 weeks, and again demonstrated a reduction in invasive fungal infections, compared with historic controls. In our center, the mean birth weight and gestational age of infants with invasive candidiasis in the control period was 786 g and 26 weeks, respectively.…”
Section: Targeted Fluconazole Prophylaxis In Preterm Infantsmentioning
confidence: 99%
“…To date there have been five randomized controlled trials (RCTs) [52,[65][66][67][68], eight retrospective reviews [19,20,[73][74][75][76][77][78], and a Cochrane review [79] examining fluconazole prophylaxis in neonates.…”
Section: Neonatal Clinical Studiesmentioning
confidence: 99%